PEMANFAATAN ICT MELALUI IMPLEMENTASI e-LEARNING BERBASIS INTEGRASI KEISLAMAN DALAM PROSES PEMBELAJARAN - Dicki Hartanto (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2018)
Even the application of e-Learning in UIN Sultan Syarif Kasim Riau has began in 2010, but in learning practice, the e-Learning has not been associated with Islamic integration as Indentifier of Islamic university. Therefore, the researcher interested to have a study, entitled